Above Ground Biomass and Carbon Stock in Some Perennial Crop Based Agroforestry Systems in the Humid Forest Zone of Cameroon - , Nkengafac Jetro Njukeng; , Ejolle Eugene Ehabe (Archives of Current Research International, 2016)
Aims: To estimate the above ground biomass and carbon stocks of Cocoa, Oil palm and Rubber based agroforestry systems in the humid forest region of Cameroon. Place and Duration: A field survey was carried out on 39 typical perennial crop-based agroforestry farms, distributed around Kumba and extending to the Bombe-Malende zones (4°25’- 4°80’ N and 9°25’- 9°35’ E) in the South West Region of Cameroon in 2009. Methodology: The main criteria for the selection of farms was that they constituted the major perennial crops (Cocoa, Oil palm or Rubber) associated with each other or with other perennial crops as well as food crops. Thirty-nine perennial crop-based agroforestry farms were selected and the number of each tree species was counted and recorded, the diameter at breast height (DBH) and approximate heights taken. Diameter measures of trees and palms were individually converted to measures of above ground biomass (AGB) based on allometric equations and carbon content was estimated as 50% of the biomass. Results: The studied farms were highly diversified with different species, which were used for food, timber or provided products that were sold. The carbon stock per unit farm varied greatly; Oil palm-based agroforestry system presented the highest above ground carbon; an average of 72.5 Mg C/ha followed by Rubber-based agroforestry system (36.3 Mg C/ha) and lastly by Cocoa-based agroforestry system (6.23 Mg C/ha). Conclusion: The studied systems stored a substantial amount of carbon besides meeting the immediate needs of the farmers such as food and income generation. The allometric equations for the estimation of biomass need to be developed for this region in order to get more reliable results.